Pertanggungjawaban Pelaku Tindak Pidana Turut Serta Melakukan Korupsi Bantuan Stimulan Perumahan Swadaya - Zulfi Diane Zaini; Angga Alfiyan; Elsa Tri Antika (Universitas Islam Balitar, Blitar, 2023)
This research is to find out the basic considerations of judges in making decisions against perpetrators of criminal acts participating in corruption, stimulant assistance for self-help housing, and their criminal responsibility, using normative juridical research methods. The results of the study show that the basis for the judge's considerations in deciding against the perpetrators of the crime of participating in the corruption of self-supporting housing stimulant assistance is based on evidence, statements from witnesses, statements from experts, indictments and charges, the elements that meet in the indictment, as well as aggravating and mitigating circumstances and criminal responsibility for the perpetrators of corruption self-help housing stimulant assistance, namely imprisonment for 1 (one) year and a fine of Rp. 50,000,000., (fifty million rupiahs) ) provided that if the fine is not paid it is replaced by imprisonment for 3 (three) months.